PELANGGARAN LALU LINTAS OLEH PENGGENDARA KENDARAAN BERMOTOR DALAM PENERAPAN TILANG ELEKTRONIK DI KOTA PONTIANAK - NIM. A1012221023, NISRINA ALISHA PUTRI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The high number of traffic violations is a recurring problem in urban areas, especially in Pontianak City. Violations such as not wearing a helmet while riding a motorcycle, using a cell phone while driving, and not wearing a seatbelt are still common, despite the fact that Pontianak City has implemented an Electronic Traffic Law Enforcement (ETLE) system at five strategic locations since 2021. The ETLE system was designed to raise public awareness that they are being monitored while driving to maintain traffic order even when no police officers are present. However, in reality, violations have increased from 1,084 cases in 2022 to 1,286 cases in 2024, with a total of 3,643 violations over the past three years. This study aims to identify and analyze the factors that cause the people of Pontianak City to continue violating traffic regulations despite the implementation of an electronic ticketing system. This research uses a sociological juridical method with a descriptive analytical approach. Data was obtained through literature studies, interviews with the Head of Traffic Division of West Kalimantan Regional Police, academics, ETLE monitoring officers, and distribution of questionnaires to 36 traffic violators. The theories used are the legal awareness theory from Soerjono Soekanto and criminology theory to analyze the behavior of violators. The research results show that there are three main factors causing the high rate of violations: (1) Low understanding of drivers regarding the ETLE system, working mechanisms, and legal consequences, especially among high school graduates who are the dominant group of violators (aged 17-25 years); (2) Society's habits and culture of being